2005
DOI: 10.1038/sj.bjc.6602673
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged fixed dose rate infusion of gemcitabine with autologous haemopoietic support in advanced pancreatic adenocarcinoma

Abstract: This study aimed to define the maximum-tolerated dose (MTD) of fixed dose rate (FDR) of gemcitabine (2 0 -2 0 -difluorodeoxycitidine) infusion with circulating haemopoietic progenitor support and to evaluate the activity of the treatment. Secondary end points were pharmacokinetic of gemcitabine and difluorodeoxyuridina (dFdU) measured at first course and the activity andexpression profile of cytidine deaminase (CdA) on circulating mononuclear cells. Patients with advanced pancreatic carcinoma received escalati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 25 publications
0
37
1
Order By: Relevance
“…Tibaldi et al (2008) suggested that the CDA 27Lys/Lys genotype predicted a better clinical benefit, a higher response rate, and longer TTP and OS compared to the other CDA genotypes. Another clinical study showed a correlation between mRNA expression of CDA in peripheral blood mononuclear cells and clinical outcome in gemcitabine-treated patients (Bengala et al, 2005). Maring et al (2010) investigated the impact of the common non-synonymous SNP in the CDA gene, CDA 27, on gemcitabine pharmacokinetics in NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tibaldi et al (2008) suggested that the CDA 27Lys/Lys genotype predicted a better clinical benefit, a higher response rate, and longer TTP and OS compared to the other CDA genotypes. Another clinical study showed a correlation between mRNA expression of CDA in peripheral blood mononuclear cells and clinical outcome in gemcitabine-treated patients (Bengala et al, 2005). Maring et al (2010) investigated the impact of the common non-synonymous SNP in the CDA gene, CDA 27, on gemcitabine pharmacokinetics in NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 A). Elevated CDA expression has been associated with poor progression rate and survival in advanced pancreatic adenocarcinoma patients treated with dFdC (36). Similar to dFdC, FAC is also susceptible to deamination (D.O.C.…”
Section: Additional Mechanisms Of Dfdc Resistance and Potential Limitmentioning
confidence: 99%
“…15 Only cells transfected with CDA are less sensitive to gemcitabine suggesting the need for very high levels of CDA activity. 16 However, clinical studies show a correlation between mRNA expression of CDA in peripheral blood mononuclear cells and clinical outcome in gemcitabine-treated patients, 17 and CDA gene expression in bone marrow mononuclear cells and hematological toxicity. 18 Similarly, the pharmacogenomics of deamination, including CDA polymorphisms, is conflicting.…”
Section: Discussionmentioning
confidence: 99%